WAYS FOR ACHIEVING THE COMPETENCES OF PHYSICAL EDUCATION IN SCHOOL BY THE CONTENT OF THE GYMNASTICS IN 5th AND 6th GRADES - Bestiuc Afanasov Maria; Leuciuc F (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The new curriculum is designed as a balance between core curriculum and school curriculum and contributes to decentralization and flexibility in curricular decisions at school level. The aim of our study is the finding opportunities to improve technology new teaching by developing training models operational, intermediate and final for practicing gymnastics lessons, models to coincide with the biomotrical and mental possibilities of the pupils in the 5th and 6th in order to conduct general and specific skills of physical education. Achieving general skills and competencies of physical education by means of gymnastics in the current curriculum has been successful to experiment group, boys and girls, within two years of practice due to the rationalization and optimization of resources for basic gymnastics, acrobatic and jumps, and thanks to achieve consistent patterns of practical training. Permanent was intended to achieve specific competences deriving from themes and are related to the school physical education competences